Kualitas Produk dan Harga dalam Mempengaruhi Minat Beli Konsumen - DYAN ARINTOWATI; Anggun Dwi Maretha (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
Technological developments and the increasingly modern era of globalization are currently driving the times and lifestyles of an increasingly modern society which has led to the development of increasingly varied and complex consumer needs. So this research is entitled "Product Quality and Price In Influencing Consumer Purchase Interest at UD. Lumpang Mebel Nganjuk". The aims of this research are 1). To find out the quality of the product has a partial effect on consumer buying interest, 2). To find out the price has a partial effect on consumer buying interest, and 3). To know product quality and price influence simultaneously on consumer buying interest. This type of research is quantitative research. The sample in this study used calculations with the slovin formula so that the number of samples in this study was rounded up to 79 respondents. Source of data in this study using primary sources with data collection techniques in the form of questionnaires. Analysis of the data used in the form of multiple linear regression analysis. Testing the hypothesis by conducting a t statistical test for partial testing and an F statistical test for simultaneous testing. The results of this study concluded that 1) product quality partially affects consumer buying interest at UD. Lumpang Mebel Nganjuk, t_count 5.617 and Sig.0.000. 2) prices partially affect consumer buying interest at UD.lumpang Mebel Nganjuk, t_count 3.301 and Sig.0.001. 3) product quality and price simultaneously affect consumer buying interest at UD. Lumpang Mebel Nganjuk, F_hitung25.084 and Sig.0.000.